Microbasin Hydrological Modeling Located in a High Andean Zone for Monthly Flows Estimation, Using GR2M, Temez and Lutz Scholtz Models (LACCEI, 2024)
In Peruvian remote areas, hydrometric stations records are limited. This limitation delays study of water resource management in high Andean zone of central-southern Peru. Therefore, in this work, hydrological modeling is carried out in Paucarbamba micro-watershed to generate flows from the pluviometric data obtained from the scarce SENAMHI pluviometric stations. These hydrological models are GR2M, Lutz Scholtz and Temez. After results analyzing, Lutz Scholtz model has a satisfactory fit with the following validation coefficients Nash = 1.00, PBIAS = 5.52 and RMSE = 0.05. In conclusion, for generation of monthly mean flows in Paucarbamba microbasin, Lutz Scholtz hydrologic model has better fit according to validation coefficients analysis.